2022
DOI: 10.7189/jogh.12.04042
|View full text |Cite
|
Sign up to set email alerts
|

Engaging women and men in the gender-synchronised, community-based Mbereko+Men intervention to improve maternal mental health and perinatal care-seeking in Manicaland, Zimbabwe: A cluster-randomised controlled pragmatic trial

Abstract: Background Maternal mental morbidity and low perinatal health service utilisation in resource-constrained settings contribute substantially to the global burden of poor maternal, newborn, and child health. The community-based Mbereko+Men program in rural Zimbabwe engaged women and men in complementary activities to improve men’s support for women and babies, coparents’ equitable, informed health decision-making, and ultimately, maternal mental health and care-seeking for maternal and newborn healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Apart from a solitary study conducted in Israel (n = 1) [ 27 ], the remaining studies were conducted in LMICs including Zimbabwe (n = 1) [ 28 ], South Africa (n = 2) [ 24 , 25 , 29 ], Pakistan (n = 3) [ 26 , 30 32 ], and India (n = 2) [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from a solitary study conducted in Israel (n = 1) [ 27 ], the remaining studies were conducted in LMICs including Zimbabwe (n = 1) [ 28 ], South Africa (n = 2) [ 24 , 25 , 29 ], Pakistan (n = 3) [ 26 , 30 32 ], and India (n = 2) [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were RCTs [ 26 , 28 , 30 32 , 34 ] (four of which were cluster-RCTs) and the remaining were quasi-experimental in design [ 24 , 25 , 27 , 29 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another intervention that was targeted for women, children and men/fathers/coparents in Mutasa district, Zimbabwe, used community-based training and discussion groups that addressed services for mothers, HIV transmissions and engaging in problemsolving therapy. Results indicated that addressing gender inequality improved maternal mental health [46]. The interesting aspect of this program included creating and implementing educational and outreach programs that encouraged "male champions".…”
Section: Program Evaluationmentioning
confidence: 99%
“…It can further be noted that through participatory interventions, mental health services inclusive of antenatal care, maternity and family planning can be improved through male-involvement. A recent study that contributed towards the current limited literature, was Comrie-Thomson et al's [46] trial on implementing a gender-synchronised intervention. Gendersynchronised interventions are conceptualised as programs that employ multiple strategies to change community norms related to gender as well as engage men to achieve gender equality and improve health [49].…”
Section: Program Evaluationmentioning
confidence: 99%
“…Considerable efforts have been made to involve men in MNCH services, however the focus has mainly been on how their involvement can improve MNCH outcomes [ 11 , 22 25 ]. Extensive research has been conducted on barriers and facilitators to men’s involvement in MNCH services, and efforts have been made to address some of the barriers, however, men’s involvement in MNCH services remains low [ 26 ].…”
Section: Introductionmentioning
confidence: 99%